EFEK MEREK DOMESTIK vs ASING DAN INFORMASI COUNTRY-OFORIGIN TERHADAP PERSEPSI DAN SIKAP KONSUMEN : Studi Perilaku Konsumen Pada Produk Susu Olahan - Syahlani, Suci Paramitasari (Journal of Indonesian Economy and Business, 2008)
The aims of this research is to identify the effect of domestic and foreignÂ branding towards consumer perceptions and attitudes, also country-of-origin (COO)Â information towards consumer attitudes. Product stimuli used in this research wasÂ processed milk product. This research was held by factorial design and paper andÂ pencil experiments are used as experiment tool. Eighty (80) males and 80 females ofÂ Gadjah Mada University students are used as respondent and then classified intoÂ four experiment groups which were domestic branding-domestic COO, domesticÂ branding-foreign COO, foreign branding-domestic COO and Foreign brandingforeignÂ COO. The analysis method employed in the study was independent sample ttestdan regression analysis. The results indicated that effect of foreign branding,Â which was English branding, showed its positive effect better on consumerÂ perceptions and attitudes of processed milk product. Consumer perception showedÂ that foreign branded processed milk product had higher quality than domesticÂ branded processed product. Positive attitudes consumer toward foreign brandedÂ processed milk product was higher than domestic branded processed milk product.Foreign COO showed higher positive consumer attitudes than domestic COO.Gender factor did not show its effect on consumer attitudes toward processed milkÂ productâs brand. This research also showed that effect of foreign branding wasÂ higher than COO information on product evaluation.Keywords: Brand, country-of-Origin, perception, attitudes.